(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The Internet of Things (IoT) ecosystem has long operated on a bifurcated model, forcing hardware developers to choose between low-power, deterministic real-time microcontrollers (MCUs) and high-performance, non-deterministic Single Board Computers (SBCs). This paper presents a comprehensive technical review and analytical evaluation of the Arduino UNO Q, a newly released system that directly addresses this division. Citing official launch documentation and verified technical briefs, the UNO Q integrates a ”dual-brain” Heterogeneous System Architecture (HSA) combining a Qualcomm® Dragonwing™ QRB2210 microprocessor (MPU) running a Debian Linux operating system with an STM32U585 real-time microcontroller (MCU). This paper details the structural layout, describes the physical domain isolation, and derives a mathematical model for Inter-Processor Communication (IPC) latency. To address the lack of live physical benchmarking, we establish a formal MultiCriteria Decision Analysis (MCDA) framework to mathematically explain system positioning, and provide three reproducible, stepby-step physical experimental testing protocols. By clarifying the boundary between confirmed hardware capabilities and proposed validation setups, this research provides an essential, rigorous baseline for evaluating this novel class of embedded edge devices.